How can "gamification" help in the teaching of arithmetic operations as a didactic tool and digital technology? - Santiago, Paulo Vitor da Silva; B, Baiduri (Delta-Phi: Jurnal Pendidikan Matematika, 2023)
This article is a teaching proposal concerning arithmetic problems of mathematics to help teachers in initial training in mathematics and teaching mathematics in the classroom with the use of Gamification. Thus, the objective of this article is to investigate what contributions didactic engineering and digital technologies using gamification in full-time high school teaching can be helpful with the contents of basic operations. The methodology applied with the games was based and structured on the Didactic Engineering research methodology, being exploratory research of a qualitative nature to familiarize the mathematical problems with the use of Digital Technologies. The results were categorized based on the phases of preliminary analysis, a priori analysis, experimentation, and a posteriori analysis and validation. Conclusions that the use of applied problems brought out the validation of the strategies applied in the classroom. Therefore, the expected results were positive in the teacher's view of the way the two games were planned in Google Presentations and in supporting the students in the teaching and learning processes of Mathematics.